Backcasting Approach to Sustainable - Stakeholders’ Perspectives on Challenges, Barriers, and Opportunities for Sustainability Transition. - Valadez Garcia, Diana; Sen, Burak (My University, 2014)
Challenges coming along with global sustainability issues, e.g. climate change, cannot be solved with conventional, linear thinking approaches. Transition towards sustainability is a non-linear process and involved a wide variety of actors. Therefore it requires in-depth understanding of barriers and drivers that disable or enable transition in the current unsustainable system. Adopting systems perspective with backcasting approach and inspired by the “think global, act local” paradox, the Challenge Lab project takes on the present challenges in the unsustainable transport system in Gothenburg, Sweden by introducing a new two-phased methodology, called ‘the Challenge Lab (C-Lab) process’, to address a societal challenge. The first phase focuses on understanding the system from different perspectives to identify critical leverage points and helps intervene in ill-structured systems. The second phase consists of a study that identifies the challenges, barriers, and opportunities in the transport system of Gothenburg, based on opinions gathered from the interviews with 10 stakeholders. These challenges, barriers and opportunities are shown on the conceptual model of the system. Unlike similar studies considering Gothenburg as the case city, the present master’s thesis covers both passenger and goods transport, and considers academy – in addition to industry and government- as another relevant stakeholder. The new methodology was useful to have a systemic understanding of the complexity and dynamics of societal challenges. The findings showed that collaboration between the stakeholders and integration of transport into the city planning are among the main challenges towards a sustainable transport system, but could become opportunities, if addressed. Main barriers identified are the limited space in the city and the politician’s fear of loss when proposing and implementing sustainable strategies. The findings also revealed that the majority of the stakeholders interviewed think that there is no or partially consensus on the vision for sustainable transport system in Gothenburg. The transition towards a sustainable transport system can be achieved by increasing dialogue among stakeholders and by having a ‘systems thinking perspective’ when planning the future transport system of the city.
Keywords: Grundläggande vetenskaper; Annan naturvetenskap; Basic Sciences; Other Natural Sciences